Analisis Butir Soal Komputer Akuntansi Kelas XI Melalui Aplikasi Anates - Citra Amanda Mustika Rani; Annisatun Nur Farida; Shelly Avrista; Luqman Hakim; Vivi Pratiwi (Nirta Learning Centre, 2024)
Evaluation of test devices must be conducted to analyze test items and develop effective learning strategies in schools. Teachers must be able to provide facilities for learning to evaluate student work results, use learning media, and master information technology as a whole. This study is oriented to analyze the advantages of Accounting Computer subject questions Phase F Class XI SMK using the Anates Application. This research method applies a qualitative description method to examine the data generated from the test questions given to SMK students in Surabaya as respondents which are then processed using the Anates application version 4.0 for Windows. The Anates program is used to measure the level of reliability, discriminating power, grouping, and distractor quality in each question item used. The results of the analysis indicate that this test has a high reliability value, good discriminating power, a very easy level of difficulty, a significant correlation, and a distractor quality that is classified as poor so that it needs improvement. The results of this analysis are expected to help teachers to create quality questions and in accordance with the expected competency standards. Thus, the use of the Anates application has proven effective in evaluating and improving the quality of Accounting Computer Element subject questions in Schools. This study also provides important insights for the development of learning evaluation quality in the field of Computer Accounting.